Air-fryer cookbook quick, healthy and delicious recipes for beginners - Tschiesche, Jenny; Winfield, Clare (London Ryland peters & small, 2022)
inspired recipes to help you make the most of your air-fryer, from snacks and fries, to meat, chichen and fish dishes and baking and desserts
101 tried and tested recipes
Keywords: Cooking (Natural foods); Cuisine (Aliments naturels); Hot air frying; Quick and easy cooking